Early childhood student-teachers’ perspectives on creativity - Michaelidou, Antonia; Pitri, Eliza (Frontiers in Education, 2022)
This study reports the finding of a qualitative case study derived from the need of two university instructors not only to revisit knowledge on creativity but to examine the views and perceptions of early childhood student-teachers about creativity. Interviewing early childhood student-teachers’ beliefs on creativity can focus on their general understanding of creativity, the traits of a creative individual, whether creativity can be developed in education, and how it could contribute to early childhood teachers’ professional development. Results provided evidence for specific misconception that early childhood student-teachers might have about creativity and its relation to teaching, and for early childhood student-teachers’ need for a framework and strategy to guide their creative instructional design and teaching.